A Neighborly Visit: A Qualitative Study on Understanding the Travel Motivations and Potential Travel Constraints of Turkish Tourists Travelling to Greece (Third Sector Social Economic Review, 2026)
In recent years, Greece, with its extensive coastline and numerous islands, has emerged as one of the most popular vacation destinations in the Mediterranean Basin. Tourism statistics from Greece reveal a significant influx of visitors from Türkiye, one of its neighbouring countries, a trend that is also supported by Turkish tourism data. Accordingly, this study aims to explore the travel patterns and motivations of Turkish tourists who have previously visited Greece, using the Push and Pull Factors framework and a qualitative research approach. In addition, the study seeks to identify potential travel constraints among those who have travelled to Greece multiple times. The qualitative study involved 17 semi-structured interviews with Turkish travellers from diverse demographics, key push and pull factors influencing travel to Greece were identified. The main push factors include a sense of relief and freedom, a desire for variety, reconnecting with cultural or emotional roots, and visiting friends or family. Among main pull factors, affordability, gastronomic elements, proximity, reference groups, cultural similarities stand out. On the other hand, potential constraints affecting the intention to revisit Greece include rising travel costs, health or age-related issues, political tensions between Türkiye and Greece, the search for alternative destinations, and a perceived decline in travel satisfaction. Therefore, understanding both motivating factors and potential constraints is essential for developing strategies aimed at sustaining and enhancing Turkish tourists’ intention to revisit Greece, while also providing insights for improving tourism destinations in Türkiye and encouraging domestic travel among Turkish tourists to similar destinations.
Keywords: Travel motivations; push and pull factors; travel constraints; Greece; Greek Islands